Vitellogenesis in the Patagonian Toothfish (Dissostichus Eleginoides) Conditioned to a Recirculating Aquaculture System - Vidal-Soto, R (Academic Press, 2021)
The Patagonian toothfish (Dissostichus eleginoides) is a new promising fish species for diversifying the aquaculture industry in Chile because of its high economic value and high international demand. However, when attempting to start aquaculture of a new species, one of the major challenges is successfully achieving conditions to reproduce them. This is particularly difficult when the information on the biology and physiology of the reproduction process of the species in question is scarce, as is the case with D. eleginoides. Additionally, female reproductive dysfunction is more prevalent under culture conditions and it is very important to have tools to evaluate the progress of oocyte maturation. Therefore, evaluation of the vitellogenesis process in addition to measuring gonadosomatic index (GSI) and oocyte diameter is an important parameter for allowing the monitoring of females from a broodstock that will spawn in the reproductive season. This study aimed to develop an enzyme-linked immunosorbent assay (ELISA) specific for the Patagonian toothfish (D. eleginoides) vitellogenine (Vtg) and quantify the plasma level in the fishes, maintained in a recirculation aquaculture system (RAS), throughout their reproductive cycle. A polyclonal antibody was prepared using the isolated major egg protein as antigen. This antibody was specific to the major plasma phosphoprotein identified as Vtg and was used to develop and standardize an indirect ELISA assay. The assay standard curve was linear from 0.1 to 1 µg/ml purified egg yolk protein and the average r2 was 0.995. We corroborated our ELISA assay by demonstrating a strong correlation between high levels of plasma Vtg obtained by the assay and the intensity of the corresponding bands in both SDS-PAGE coomassie stained gels and Western Blot. During the two reproductive seasons analyzed, the highest Vtg plasma level was obtained in the majority of the females in the last three months before spawning (December-January). This differs from the wild population in which the spawning occurs during the austral winter (June-September). Therefore, the RAS condition established to maintain in captivity the D. eleginoides allows females to develop mature oocytes normally, as was evidenced by picks of Vtg plasma levels. © 2021 Elsevier Inc.